Guest

Simplify combining like terms: 5x2 y – 5x2 + 3yx2 – 3y2 + x2 – y 2 + 8xy2 – 3y

 Simplify combining like terms:
5x2 y – 5x2 + 3yx2 – 3y2 + x2 – y 2 + 8xy2 – 3y

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5963 Points
2 years ago
Dear Student

When term have the same algebraic factors, they are like terms.
Then,
= 5x^2y + 3yx^2–5x^2+ x^2–3y^2–y^2–3y^2
= x^2y (5 + 3) + x^2(- 5 + 1) + y^2(-3–1 -3) + 8xy^2
= x^2y (8) + x^2(-4) + y^2(-7) + 8xy^2
= 8x^2y - 4x^2–7y^2+ 8xy^2

Thanks

Think You Can Provide A Better Answer ?